THE EFFECT OF DIFFERENT SALINITY ON THE GROWTH AND SURVIVAL OF VANNAMEI SHRIMP (Litopenaeus vannamei) IN SUKAMARA REGENCY - Wahyu Wira Pratama; M. Faiq Ash Shidiq; Rahmad Hidayat; Dwiayu Juliati Djuko; Arini Resti Fauzi; Ayu Rahmadhani; Muchammad Andi Ali Ridho (Universitas Mataram, 2026)
Vannamei shrimp (Litopenaeus vannamei) is one of the world's leading aquaculture commodities. Sukamara Regency is a leading regency for whiteleg shrimp cultivation in Central Kalimantan Province. Vannamei shrimp are euryhaline organisms, meaning they can survive in salinities ranging from 0.5 to 50 ppt, but optimal growth is generally reported to be in the range of 15 to 25 ppt. Shrimp's osmoregulation mechanism allows them to adjust their body's osmotic pressure to the environment, but this process requires extra energy. At salinities outside the optimal range, energy allocated for growth is diverted to maintaining ion balance, thus reducing growth rate. This study aimed to examine the effect of different salinities on the growth and survival of whiteleg shrimp. This research was conducted at the PSDKU Sukamara Fish Farming Laboratory and Workshop over a four-month period, from preparation to data analysis. The method used in this study was a completely randomized design consisting of 3 different salinity treatments and 4 replications. The highest growth performance results were found in P3 (salinity 20 ppt) followed by P2, and P1. While survival did not show any significant difference, with the highest survival rate in P3 treatment at 85%, followed by P1, and P2 at 75%. Water quality parameters showed that the water quality of cultivated fish was still in optimal condition, which showed that the temperature ranged between 26-28 oC, pH ranged between 7.8-8.2, and DO ranged between 10.4-10.9 mg/L.